Neurocysticercosis research in Mexico: A bibliometric analysis of the Instituto Nacional de Neurología y Neurocirugía Manuel Velasco Suárez - Rubio, Carmen; Rodríguez-Quintero, Paola; Fleury, Agnès; Suástegui-Román, Roberto Alfonso; Bowles, Brigham; González-Garibay, Guillermo; Pacheco-Aispuro, Gerónimo; Lee, Ángel (Frontiers in Tropical Diseases, 2022)
Neurocysticercosis (NCC), is the most common neglected parasitic disease of the central nervous system and leads to many economic and health issues in endemic and non-endemic countries. A bibliometric analysis would shed light on the evolution and development of research in this field, and this is the first study on NCC research. Our institution in Mexico City, the Instituto Nacional de Neurología y Neurocirugía Manuel Velasco Suárez (INNN), has set some milestones on the management of Neurocysticercosis and has a decade-long experience and such an analysis in an endemic country like Mexico will be beneficial. We tracked the scientific output in Scopus, from its foundation to March 2021. The studied variables were: article type, number of citations, area (clinical/ experimental), chronological profile and preferred journals. In the period from 1964 to 2021, from a total of 3,166 articles from the institution, 232 papers are related to neurocysticercosis with a total of 7,155 citations. The trending topics in the clinical area are pharmacology, and pathology in the experimental papers. The number of articles has steadily increased but NCC is currently a neglected topic that needs further research to better address disease burden and allow its eradication.